2015
DOI: 10.5194/bg-12-7087-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ash leachates from some recent eruptions of Mount Etna (Italy) and Popocatépetl (Mexico) volcanoes and their impact on amphibian living freshwater organisms

Abstract: Leaching experiments were carried out on fresh ash samples from Popocatépetl 2012, Etna 2011, and Etna 2012 eruptions, in order to investigate the release of compounds in both double-deionized and lake (Lake Ohrid, FYR of Macedonia) waters. The experiments were carried out using different grain sizes and variable stirring times (from 30 min to 7 days). Results were discussed in the light of changing pH and release of compounds for the different leachates. In particular, Etna samples induced alkalinization, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 43 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…The high TOC / TN ratios are therefore most likely a result of early digenetic selective loss of N (cf. Cohen, 2003). The aquatic origin of the OM in the sediments of the deep basin of Lake Ohrid is also in agreement with the results of Rock Eval pyrolysis from the nearby LINI drill site (Lacey et al, 2015a; see Fig.…”
Section: Hemipelagic Sedimentssupporting
confidence: 87%
See 2 more Smart Citations
“…The high TOC / TN ratios are therefore most likely a result of early digenetic selective loss of N (cf. Cohen, 2003). The aquatic origin of the OM in the sediments of the deep basin of Lake Ohrid is also in agreement with the results of Rock Eval pyrolysis from the nearby LINI drill site (Lacey et al, 2015a; see Fig.…”
Section: Hemipelagic Sedimentssupporting
confidence: 87%
“…Mixing also leads to oxidation of OM at the sediment surface and, thus, to lower TOC contents. TOC preservation in the sediments can also be modified by lake-level fluctuations, as oxidation of OM starts in the water column during settling (Cohen, 2003;Stockhecke et al, 2014b). However, distinct climate-induced lake-level fluctuations such as, for example, described for the Younger Dryas at Lake Van in Turkey (Wick et al, 2003;Stockhecke et al, 2014b, and references therein) have not been observed at Lake Ohrid in previous studies covering the last glacial-interglacial cycle (cf.…”
Section: Hemipelagic Sedimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…High-resolution studies of diatoms in both lake sediment records indicate little evidence for a response of the diatom community related to the H4 event, but they do show a clear and rapid change following tephra deposition . This strong change is likely due to fertilisation and the availability of nutrients, particularly silica, such as it was shown in laboratory studies and leaching experiments of tephra with Lake Ohrid water (D'Addabbo et al, 2015). After the initial response, diatom community compositions in lakes Ohrid and Prespa returned to their quasi pre-disturbance state.…”
Section: Sub-orbital Changesmentioning
confidence: 86%
“…Cvijić, 1911;Aliaj et al, 2001;Dumurdzanov et al, 2004;Reicherter et al, 2011;Lindhorst et al, 2015). There is little consensus on the limnological origin of the lake itself, however.…”
Section: Originmentioning
confidence: 99%